2017
DOI: 10.4103/jpn.jpn_31_17
|View full text |Cite
|
Sign up to set email alerts
|

Profile and outcome of pediatric brain tumors – Experience from a tertiary care pediatric oncology unit in South India

Abstract: Context:Tumors of the central nervous system (CNS) constitute the second most common pediatric cancers. Unlike leukemia, management of CNS tumors requires a good multidisciplinary team. Higher rates of treatment abandonment are documented in view of complexity of the treatment with long duration, involving neurosurgery, radiation, chemotherapy, and high cost of treatment. Morbidity associated with CNS tumors may be significant in terms of physical deficits as well as neuropsychological and neuroendocrine seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
25
1
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 31 publications
5
25
1
5
Order By: Relevance
“…On the other hand, an Iranian study with 198 children found that 63.1% (125) corresponded to the male gender, a result that is consistent with that reported by Azad et al 15 . As for clinical manifestations, headache and hemiparesis were the most frequently reported symptoms by Azad et al 14 , with 27% and 24.3% respectively, which are figures comparable with the data observed by our team, where the main symptoms were headache and nausea and/or vomiting with 41.2% and 29.4%, respectively, in contrast with the study conducted by Suresh et al 16 in southern India, where the main symptom was vomiting, with 62.5%, followed by headache in 37.5%. In concordance with Suresh et al 16 findings, in the study by Faranoush et al 15 , vomiting (n = 106, 53.5%) and headache (n = 102, 51.5%) were the main clinical findings.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…On the other hand, an Iranian study with 198 children found that 63.1% (125) corresponded to the male gender, a result that is consistent with that reported by Azad et al 15 . As for clinical manifestations, headache and hemiparesis were the most frequently reported symptoms by Azad et al 14 , with 27% and 24.3% respectively, which are figures comparable with the data observed by our team, where the main symptoms were headache and nausea and/or vomiting with 41.2% and 29.4%, respectively, in contrast with the study conducted by Suresh et al 16 in southern India, where the main symptom was vomiting, with 62.5%, followed by headache in 37.5%. In concordance with Suresh et al 16 findings, in the study by Faranoush et al 15 , vomiting (n = 106, 53.5%) and headache (n = 102, 51.5%) were the main clinical findings.…”
Section: Discussionsupporting
confidence: 89%
“…As for clinical manifestations, headache and hemiparesis were the most frequently reported symptoms by Azad et al 14 , with 27% and 24.3% respectively, which are figures comparable with the data observed by our team, where the main symptoms were headache and nausea and/or vomiting with 41.2% and 29.4%, respectively, in contrast with the study conducted by Suresh et al 16 in southern India, where the main symptom was vomiting, with 62.5%, followed by headache in 37.5%. In concordance with Suresh et al 16 findings, in the study by Faranoush et al 15 , vomiting (n = 106, 53.5%) and headache (n = 102, 51.5%) were the main clinical findings. The indications for performing a neuroimaging examination are based on the index of suspicion with regard to the signs and symptoms observed in a patient; therefore, in every child with persistent headache (continuous or recurrent, for more than 4 weeks), a CNS tumor should be suspected, and neuroimaging examination is required to rule it out 17,18 .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…No studies attempted to formally analyze predictors of treatment abandonment in CNS tumors. However, authors of 12 studies reported possible causes of abandonment (Table ), based on their personal experience with patients, patient records, and knowledge of patients’ backgrounds . Only one (Chinese) study conducted a questionnaire with caregivers to identify reasons for abandonment .…”
Section: Overall Resultsmentioning
confidence: 99%
“…Diagnostic and treatment protocols vary across the world due to—among other things—financial and logistic factors . Ultimately, these inconsistencies can result in a disparity of survival rates and HRQL . As such, it would be interesting to see if our results would differ if low to middle income countries were included.…”
Section: Discussionmentioning
confidence: 99%